Mesenteric lipoma presenting as small bowel volvulus - R.O. Alsayegh; R. Almutairi; E. Taqi; A. Alnaqi (Elsevier, 2019)
Many patients will present to the emergency department with bowel obstruction, and here we report a 4-year-old girl, who presented to the pediatric surgery service with intermittent abdominal pain and bilious emesis. Her imaging studies showed a picture of small bowel volvulus without bowel ischemia, with a soft tissue, benign-looking, mesenteric mass, most likely mesenteric lipoma. This case report documents a rare cause of small bowel obstruction in the pediatric age group. Keywords: Mesenteric lipoma, Small bowel volvulus, Pediatric surgery